Moderating Effect of Collaboration in the Relationship Between Training and Teachers Engagement in the Secondary Schools of Nepal - Tamang, Sushma; Mishra, Anjay Kumar; Ghosh, Abhijit (Chaturbhujeshwar Academic Journal, 2025)
This study explores the critical role of teacher engagement in enhancing teaching performance and student academic achievement in secondary schools in Kathmandu, Nepal. Recognizing that engaged teachers are motivated and dedicated, this research examines the moderating effect of teamwork on teachers’ engagement following professional training. Data were collected from a sample of 320 teachers from both public and private schools and analyzed using descriptive statistics in SPSS and Structural Equation Modeling (SEM) in AMOS. Findings reveal a significant positive relationship between teacher training and professional development, confirming that training directly influences teacher engagement. However, teamwork as a moderating factor did not show a significant catalytic effect on enhancing engagement post-training. This study contributes to the literature by identifying potential gaps in the translation of training into engagement through teamwork, offering new insights into the challenges of fostering collaborative practices that support teacher development in the Nepalese educational context.